Software Development for Smart Home Process Control - Kopeliuk, Vitalii Oleksandrovych; Voronytska, Vira; Havryliuk, Volodymyr (Моделювання, керування та інформаційні технології, 2019)
Smart home technology, an application of Internet of Things (IoT), provides households with e.g., comfort, control and convenience. The technology has been around for sometimes, but its prevalence is not yet widespread, and thus the potentials have largely been underestimated. The purpose of this paper is to develop a comprehensive model that can explain a large percentage of variance in the intention to use smart home technology.